2014
DOI: 10.1107/s2053229614002447
|View full text |Cite
|
Sign up to set email alerts
|

The structural properties of a noncentrosymmetric polymorph of 4-aminobenzoic acid

Abstract: The crystal structure of a polymorph of 4-aminobenzoic acid (PABA), C7H7NO2, at 100 K is noncentrosymmetric, as opposed to centrosymmetric in the structures of the other known polymorphs. The two crystallographically independent PABA molecules form pseudocentrosymmetric O-H...O hydrogen-bonded dimers that are further linked by N-H...O hydrogen bonds into a three-dimensional network. The benzene rings stack in the b direction. The CO2 moieties are bent out slightly from the benzene ring plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Surface and morphological data shown in yellow. polymorph, this has an orthorhombic crystal structure, which was found by crystallising from aqueous solutions containing pABA and selenous acid, 48 but this latter structure was not considered here. Both the α and β crystal structures are monoclinic with a P2 1 /n space group.…”
Section: Methodsmentioning
confidence: 99%
“…Surface and morphological data shown in yellow. polymorph, this has an orthorhombic crystal structure, which was found by crystallising from aqueous solutions containing pABA and selenous acid, 48 but this latter structure was not considered here. Both the α and β crystal structures are monoclinic with a P2 1 /n space group.…”
Section: Methodsmentioning
confidence: 99%
“…Of the latter it would appear that AMBNAC06 has its amine hydrogens incorrectly positioned so as to make the nitrogen trigonal, rather than the correct pyramidal. In 2014 Benali-Cherif et al 22 reported a new noncentric polymorph, γ, having a dimer motif similar to α but differing slightly in its packing. Reported in the preceding companion paper to this review Ward et al provide details of a new polymorph, δ, produced under high pressure crystallisation conditions.…”
Section: The Crystal Structures Of Paba Polymorphsmentioning
confidence: 99%
“…In their original paper Benali-Cherif et al obtained it as needles from water in the presence of selenous acid. 22 Given its structural similarity to α, it is expected that such needles will also reflect the stacking interaction along the b-axis. More recently Kamali et al 49,50 have reported failure to reproduce the crystallisation of the γ form from either selenous or phosphinic acids but have found that its preparation using a vapour growth technique is rather facile.…”
Section: β δmentioning
confidence: 99%
“…Sublimation onto a form II template gave only form II on the template, Figure 7 and Figure S5. 44,45 The other form for which a crystal structure is available is numbered form V. 46 This was crystallized from selenous acid solution and it appears to have been a fortuitous crystallization. Attempts to reproduce the crystallization of PABA form V from selenous acid at concentrations up to 10% gave only the hydrated salt (H3NC6H4CO2H) + (HOSeO2)ˉ.H2O.…”
Section: Carbamazepine Form Vmentioning
confidence: 99%